Writing essentials - Rodrigues, Dawn.; Tuman, Myron C. (New York : W. W. Norton, 1999)
This book is about: Writing essays online; Research; Documentation; Basic Document design; Sentences and Words; Grammar; Punctuation; Mechanics.
Keywords: English language; Rhetoric; Report writing; English language -- Rhetoric -- Data processing -- Handbooks, manuals, etc; Report writing -- Data processing -- Handbooks, manuals, etc